EVOLUTION OF CHEMICAL COMPOSITION AND CRYSTAL MORPHOLOGY OF AEGIRIN DURING FORMATION OF THE VISHNEVOGORSK ALKALINE CARBONATITE COMPLEX (SOUTH URALS) - E.P. Makagonov; S.A. Repina; V.A. Kotlyarov (Минералогия, 2018)
The chemical composition and crystal morphology of aegirine changed during formation of the Vishnevogorsk alkaline carbonatite complex. Fenitization of host metamorphic rocks, early vein syenites and pegmatites resulted in crystallization of pyroxenes with minimal content of aegirine end-member (up to 57 %) and primitive «hedenbergite» cut. Aegirine of this type is accompanied by alanite-(Ce). During next period (formation of syenite-pegmatites and carbonatites), aegirine crystals were supplied by additional prism and the amount of aegirine end-member reached 70 %. The rocks of the pegmatite stage are characterized by the higher amount of pyrochlore. Aegirine of the Alpinetype veins changes its crystal habit from prismatic to long-prismatic with flat and sharp apices, respectively. The color of crystals varies from green-black to green. The crystals with sharp apices are most diverse in respect to simple forms showing vertical prisms {hk0} in combination with forms {hh1} and {hk1} with polar coordinates r 65° and more. BSE images of them demonstrate zonalsectorial structure and phantom inclusions of pyroxenes of early generations. The amount of aegirine end-member attains 98 %. The increase in Na content is accompanied, first, by the increase and, then, the decrease in the Fe content. The Ca, Mg, Al and Mn contents decrease with increasing Na component, whereas the Ti and V contents increase. Aegirine of the Alpine-type veins is associated with minerals of rare earth elements and rare metals.